Classroom-based assessment. (January 2021) - Lewkowicz, Jo; Leung, Constant
Abstract : The assessment of students in the classroom has been going on since time immemorial. What is comparatively recent, however, is the systematic study of classroom-based assessment (CBA). The term 'CBA' has been putatively linked to Michael Scriven's (1967) work on formative and summative evaluation. However, current interest in such assessment and how it is enacted has, to a large extent, been prompted by shifts in educational policy in various contexts and evolving education systems. This, in turn, has led to the increase in research activity that is detailed in the timeline that follows. At the same time, considerable effort has been exerted by various governments and professional associations into the development of CBA frameworks, but as publications related to these are not strictly research documents, a separate list of examples is provided as supplementary material.